Projeto Especial de Ação: contribuições das pesquisas do Mestrado Profissional em Educação – Formação de Formadores - Gomes, Elizete (2021)
This research, with a qualitative approach, had as general objective to analyze the contributions from the research carried out in the Professional Master's Degree in Education: Education training for trainers (Formep), at Pontifícia Universidade Católica de São Paulo (PUC-SP), between 2015 and 2020, related to the Special Action Project (Projeto de Ação Especial - PEA), of the Municipal Education Secretary of São Paulo, for the teachers´ continuing education. From the general objective, the following specific objectives were set: (1) to analyze the research developed at Formep that addressed the topic of the PEA; (2) to identify the contributions of the research to the trainer's practice in the PEA, according to the view of the selected researchers and (3) to collate the presence of changes in the organization and in the education training carried out in the PEA, including the period of the sanitary crisis caused by the Covid-19 pandemic, in the view of the studied researchers. The conduct of this research was justified by the fact that PEA is the main education training in the educational unities of Municipality of São Paulo. In the survey of correlated research that addressed the theme, studies developed by Formep´s graduates were identified. It was considered important not only to know what the research conducted addressed on the PEA, but especially to investigate the outspreading and repercussions of these studies in the context of the referred Project. The concept of “pedagogical coordination” was supported by the studies of Almeida (2012; 2013; 2017), Borges (1999), Domingues (2009), Placco and Almeida (2009), Placco (2008), Placco and Souza (2006) and Souza (2012), and the concept of “experience” and “education training” were supported by Josso (2004), Larrosa (2002) and Passegi (2011; 2020). Specific documents and legislation from the São Paulo Municipal Secretary of Education were also analysed. The research subjects were two Formep´s graduates, professionals of São Paulo public education network. The data collection was conducted through survey and mapping of Formep´s research and narrative interviews. To the data analysis, document analysis (LÜDKE; ANDRÉ, 1986) and analysis of prose (ANDRÉ, 1983) were used. Among the results, the process of building the object of study of the research developed at Formep, the resignifications of the PEA's regard and education training moment and the relation of the knowledge constituted in the research with the performance in the project were highlighted. The results enabled us to conclude that, through the production of research carried out in Formep on the subject, the graduates redimensioned their pedagogical performances in relation to the education training moment of the PEA, with emphasis on the appreciation of the participants´ life stories, the regard at the achievement of this training moment as a result of the teaching class struggle, the education training in a humanized, collaborative and promoting way of belonging and valuing the group´s constitution, with the participation of the director and assistant director in the training project. The spread of discussions on the teachers´ practices in these training moments, identified in the dissertations and in the narratives of the graduates of the master’s program, showed how they reverberate in the quality of Basic Education